Playing as musicking: an exploration of ergodic musicking through gameplay - Valentim, Luís Miguel Goulart (2023)
Playing music and playing games are two distinct forms of play that however share some operational similarities and possess a rich history together, having many times in the past intertwined to create fruitful solutions. The present study proposes there is a multidisciplinary play space to explore at the intersection of playing games and playing musical instruments, which we approach through the lenses of the ergodic musicking paradigm and game design. We explore this concept in theory and in practice, resorting to the available literature, interviews from experts, artifact analysis, and developing a prototype of our own. This study’s results consist of a knowledgebase on ergodic musicking through games, a systematization of parameters for ergodic musicking game development, and prototypes of ergodic musicking games. The results of this dissertation lead us to believe ergodic musicking gameinstruments may provide an alternative option to classical musicking means, which may bring benefits on the fields of musical improvisation, experimentation, performance, and pedagogy.